2002
DOI: 10.1002/pola.10189
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of fluorinated polyimides. 1. Derived from novel 4,4″‐bis(aminophenoxy)‐3,3″‐trifluoromethyl terphenyl

Abstract: A new diamine monomer, 4,4″‐bis(aminophenoxy)‐3,3″‐trifluoromethyl terphenyl (ATFT) was synthesized that led to a number of novel fluorinated polyimides by solution as well as thermal imidization routes when reacted with different commercially available dianhydrides like pyromellatic dianhydride (PMDA), benzophenone tetracarboxylic acid dianhydride (BTDA), or 2,2‐bis(3,4‐dicarboxyphenyl) hexafluoropropane (6FDA). The polyimides ATFT/BTDA and ATFT/6FDA derived from both routes were soluble in several organic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 82 publications
3
80
0
Order By: Relevance
“…Recent studies demonstrated that polyimides derived from ether-bridged aromatic diamines with trifluoromethyl (-CF 3 ) groups are soluble high-temperature polymeric materials with low-moisture uptake, low dielectric constant, high optical transparency and low birefringence. [22][23][24][25][26][27][28][29] Imidazole ring is a useful n-type building block with high-electron affinity and good thermal stability and has been successfully incorporated in small molecules and polymers as the electron-transport component of OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that polyimides derived from ether-bridged aromatic diamines with trifluoromethyl (-CF 3 ) groups are soluble high-temperature polymeric materials with low-moisture uptake, low dielectric constant, high optical transparency and low birefringence. [22][23][24][25][26][27][28][29] Imidazole ring is a useful n-type building block with high-electron affinity and good thermal stability and has been successfully incorporated in small molecules and polymers as the electron-transport component of OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility behavior of these copolyimides did not show significant improvements in comparison to their homopolymer analogs. 6 This was possibly due to the formation of random copolyimide structures. Park et al 24 observed drastic differences in solubility between alternating copolyimides and their corresponding random isomers.…”
Section: Polymer Solubilitiesmentioning
confidence: 99%
“…5 Thus, the polyimides based on trifluoromethyl groups have been reported to be soluble in amide, ketones, and chlorinated hydrocarbons. 6,7 Other means of solubilization of polyimides includes the introduction of flexible linkages, 8,9 bulky substituents, 10,11 or bulky units in the polymer backbone [12][13][14] or noncoplanar 15,16 or alycyclic 17 monomers. ODA is widely used in the synthesis of polyimides, but the polyimides synthesized from this diamine are insoluble or have poor solubility, depending on the dianhydride used.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it had also been proved that polyimide contained the trifluoromethyl or ether group can enhance the solubility and thermal stability, reduce dielectric constant and moisture absorption, and raise the optical transparency. [18][19][20][21][22] In this study, the bis(ether anhydride) I was prepared and a series of novel poly(ether imide)s (III) were prepared from I with CF 3 -contained diamines II a{g . These polymers were investigated in regard to their solubility, color, optical transparency, dielectric property, and moisture absorption, and they were compared to analogous non-fluorinated poly(ether imide)s IV.…”
mentioning
confidence: 99%